Plasma formation in a pseudospark discharge - LUNNEY, JAMES GERARD (IEEE, 1989)
Unique features associated with the hollow cathode recess in a pseudospark discharge have been identified from streak camera observations. A plasma is observed to form in a highly localized region immediately behind the cathode aperture prior to gas breakdown in the main discharge volume. The point-like plasma expands from an initial diameter of below 0.3 to 3 mm, the size of the cathode aperture, in about 20 ns, at which time the main discharge is formed starting from the axis. Numerical modeling based on swarm parameters has been carried out to investigate the plasma formation in the hollow cathode region. Results show that a combination of varying ionization rates due to the field geometry and differing mobilities of electrons and ions leads to the formation of a highly localized space-charge field on axis behind the hollow cathode. This space-charge field in turn brings about the rapid formation of a highly localized, high density of charge carriers behind the cathode aperture. It is suggested that this point-like formation of a plasma source is the phenomenon observed in the streak camera observation of the hollow cathode region.
PUBLISHED
Keywords: Physics